The economic impact of Ukraine’s trade relations with the EU amid geopolitical challenges: an analysis of trade dynamics, restrictions and integration - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O.; Yakubovskiy, Sergey; Truba, Arina (My University, 2024)
This article analyzes the economic implications of Ukraine’s foreign trade relations with the European Union (EU) amidst the ongoing geopolitical conflict with Russia. Using a vector autoregression (VAR) model and the Granger causality test, the study investigates the statistically significant impact of Ukraine’s merchandise exports and imports to the EU on its national GDP from 2005 to 2023. The findings reveal that exports, particularly in countries like the Netherlands, Romania, and Bulgaria, have the most substantial effect on Ukraine’s GDP. Despite infrastructural damages, trade disruptions, and unilateral trade restrictions from countries like Poland, Ukraine’s reliance on the EU for both exports and imports continues to play a critical role in the nation’s economic resilience and recovery. The article also highlights the EU’s efforts to support Ukraine through initiatives like the Black Sea Grain Initiative and Solidarity Lanes. However, ongoing challenges, including logistical constraints and political tensions, hinder further integration and economic growth. У цій статті аналізуються економічні наслідки зовнішньоторгівельних відносин України з Європейським Союзом (ЄС) в умовах триваючого геополітичного конфлікту з Росією. Використовуючи модель векторної авторегресії (VAR) і тест причинності Грейнджера, дослідження досліджує статистично значущий вплив експорту та імпорту товарів до ЄС з України на національний ВВП з 2005 по 2023 рр. Результати показують, що експорт, особливо в таких країнах, як Найсуттєвіший вплив на ВВП України мають Нідерланди, Румунія та Болгарія. Незважаючи на пошкодження інфраструктури, збої в торгівлі та односторонні торговельні обмеження з боку таких країн, як Польща, залежність України від ЄС як щодо експорту, так і імпорту продовжує відігравати вирішальну роль у економічній стійкості та відновленні країни. У статті також висвітлюються зусилля ЄС щодо підтримки України через такі ініціативи, як Black Sea Grain Initiative та Solidarity Lanes. Однак поточні виклики, включаючи матеріально-технічні обмеження та політичну напруженість, перешкоджають подальшій інтеграції та економічному зростанню.
Tuliakov V. The economic impact of Ukraine’s trade relations with the EU amid geopolitical challenges: an analysis of trade dynamics, restrictions and integration / V. Tuliakov, S. Yakubovskiy, A.Truba // InterEULawEast : Journal for the international and european law, economics and market integrations. 2024. Vol. 11. No. 2. P. 149-163. Режим доступу: https://doi.org/10.22598/iele.2024.11.2.7 ; https://hrcak.srce.hr/327006
Keywords: the EU; foreign trade; GDP; economic integration; trade restrictions; Ukraine; Україна; ЄС; зовнішня торгівля; ВВП; економічна інтеграція; торгові обмеження